Integrasi Filsafat Matematika dan Teknologi Informasi untuk Meningkatkan Pemahaman Siswa dalam Pembelajaran - Saputra, Surya Adi; Tarso, Tarso; Siswanto, Deny Hadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
This study aims to explore the concepts of the philosophy of mathematics and the teaching models applied in mathematics education from the perspective of educational philosophy. The research analyzes various sources related to philosophy, philosophy of education, philosophy of mathematics, and their connection to teaching models, including those based on Information Technology. Data was collected from secondary sources, such as books, articles, and accredited journals published between 2019 and 2024. The research method employed is a literature review with a qualitative approach, focusing on the analysis of references related to the study of philosophy, educational philosophy, and mathematics teaching models linked to philosophy and Information Technology. The findings reveal that: 1) the philosophy of mathematics plays a crucial role in enhancing the quality of mathematics education; 2) mathematics teaching models should be connected to educational philosophy through the application of real-life concepts; and 3) the integration of Information Technology in teaching models supports the effectiveness of the learning process. This study is expected to contribute by providing insights into the role of the philosophy of mathematics in the context of Information Technology-based teaching models.